Предмет: Математика,
автор: anastasia51751
Решите уравнение:
1) (x + 3)4 – 3 (x + 3)2 – 4 = 0; 2) (6x – 7)4 + 4(6x – 7)2 + 3 = 0
Ответы
Автор ответа:
2
Ответ:
х=4; х=1.125
Пошаговое объяснение:
4х+12-6х-18-4=0
4х-6х=-12+4
-2х=-8
х=-8/-2
х=4
24х-28+48х-56+3=0
24х+48х=28+56-3
72х=81
х=81/72
х=1.125
Похожие вопросы
Предмет: Английский язык,
автор: BabyJustLove
Предмет: Другие предметы,
автор: Аноним
Предмет: Українська мова,
автор: 17022000d
Предмет: Литература,
автор: Liana11199
Предмет: Биология,
автор: liza2514